Penerapan Pembelajaran Student Teams Achievent Division (STAD) Berbasis Quizizz Pada Mata Pelajaran Dasar-Dasar Ketenagalistrikan - Mimi Mimi; Doni Tri Putra Yanto (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2026)
This study aims to implement the Student Teams Achievement Division (STAD) learning model based on Quizizz and to analyze students’ learning motivation and self-efficacy in the Basic Electricity subject at SMK Negeri 1 Bukittinggi. This research employed a quantitative method with a quasi-experimental approach using a Non-Equivalent Control Group Design. The participants were tenth-grade students of the Electrical Power Installation Engineering (TITL) program, divided into an experimental class and a control class. The research instruments consisted of learning motivation and self-efficacy questionnaires using a five-point Likert scale administered before and after the treatment. The data were analyzed using descriptive statistics to identify trends in students’ learning motivation and self-efficacy. The results indicate that the implementation of the STAD learning model based on Quizizz improved students’ learning motivation and self-efficacy compared to conventional learning. Students in the experimental class demonstrated higher engagement, better self-confidence, and greater enthusiasm during the learning process. Therefore, STAD learning based on Quizizz can be considered an effective and innovative learning strategy to enhance students’ learning motivation and self-efficacy in the Basic Electricity subject.